2016
DOI: 10.3390/cryst6120159
|View full text |Cite
|
Sign up to set email alerts
|

Gas Source Techniques for Molecular Beam Epitaxy of Highly Mismatched Ge Alloys

Abstract: Ge and its alloys are attractive candidates for a laser compatible with silicon integrated circuits. Dilute germanium carbide (Ge 1−x C x ) offers a particularly interesting prospect. By using a precursor gas with a Ge 4 C core, C can be preferentially incorporated in substitutional sites, suppressing interstitial and C cluster defects. We present a method of reproducible and upscalable gas synthesis of tetrakis(germyl)methane, or (H 3 Ge) 4 C, followed by the design of a hybrid gas/ solid-source molecular bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Recently Stephenson et al [3] presented a route to overcome this problem, using a hybrid gas/solid-source MBE approach with tetrakis(germyl)methane (4GeMe) as the C source, a molecule that has one C atom bonded to four Ge atoms. This allowed growth of high quality Ge:C alloys in the composition range of 0.2% C [11].Their measurements were accompanied by density functional theory (DFT) calculations on Ge 127 C 1 supercells, indicating that Ge:C at 0.78% C is a direct gap material. These recent experimental and theoretical investigations suggest that Ge:C could therefore be a promising candidate for future silicon-based technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Stephenson et al [3] presented a route to overcome this problem, using a hybrid gas/solid-source MBE approach with tetrakis(germyl)methane (4GeMe) as the C source, a molecule that has one C atom bonded to four Ge atoms. This allowed growth of high quality Ge:C alloys in the composition range of 0.2% C [11].Their measurements were accompanied by density functional theory (DFT) calculations on Ge 127 C 1 supercells, indicating that Ge:C at 0.78% C is a direct gap material. These recent experimental and theoretical investigations suggest that Ge:C could therefore be a promising candidate for future silicon-based technologies.…”
Section: Introductionmentioning
confidence: 99%
“…36 Consistent with this analysis, Park et al 37 showed that it would be virtually impossible to achieve fully substitutional growth of Ge 1−x C x alloys by conventional molecular beam epitaxy (MBE) techniques. Recently, Stephenson et al 38 presented a route to overcome this problem, using a hybrid gas/solid-source MBE approach with tetrakis(germyl)methane (4GeMe) as the C source, a molecule that has one C atom bonded to four Ge atoms. This enabled growth of high quality Ge 1−x C x alloys having C compositions x ≈ 0.2% C. 24 These samples have been characterised using structural techniques and photo-modulated reflectance spectroscopy, 24 but there has to date been no reports of optical emission.…”
Section: Introductionmentioning
confidence: 99%